Survey of Physical Fitness Levels of Badminton Athletes in Binjai City, Indonesia - Devi Catur Winata; BASTANTA MUJIRIAH P.A (JUMORA: Jurnal Moderasi Olahraga, 2021)
Athletes aged 16-19 years is a period towards the peak of achievement that is important to be evaluated from various components including the level of physical fitness. Especially in the sport of badminton, the physical fitness aspect is an important component that must be owned for single and doubles athletes. This research aims to find out the level of physical fitness of badminton athletes in Binjai City, Indonesia. Participants in this study were 10 athletes (ages 16-19 years) at Pusdiklat PB Rada Kota Binjai Indonesia in 2021.  The design of this study is descriptive quantitative. The instruments used are physical fitness tests which include a 60-meter running test, elbow hanging test, sitting baring test, upright jump test and 1200-meter running test. Research data collection techniques using test and measurement provisions in physical fitness test guidelines. Data analysis techniques that are through quantitative data obtained are analyzed descriptive statistics, further interpreted in the category of assessment of the physical fitness component of athletes. The results showed that the level of physical fitness with a range of results of 14-17 showed a good category of 7 people (85%) and with a range of results of 10-13 showed a category of less than 3 people (25%). So based on the results of research it can be concluded that the level of physical fitness of Badminton Pusdiklat PB Rada Kota Binjai in 2021 is categorized as Good. This research has implications for badminton coaches determining physical exercise programs, techniques, and tactics so that they can be optimal in improving the achievement of their athletes. The contribution of this research is to provide an overview of future research to be able to provide a variety of exercise programs to the optimization of physical fitness of athletes. Keywords: Physical Fitness, Athlete, Badminton, Survey